Korelasi Lokasi tumor terhadap derajat keparahan Fatigue pada pasien Tumor Otak - HERMANDITA T, FEBRIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Brain tumors remains a disease with high prevalence rates each year. Research recently began looking for the cause of which can degrade is able to provide life. Several studies have found fatigue as a cause of decreased quality of life with a percentage of more than 80%, and professionals still lack an understanding of fatigue and ennobled so many untreated. One of the causes of fatigue is the location of the tumor, but the research on how much the location of the tumor affects the severity of fatigue is still limited. This study used a cross-sectional method. Subjects were patients admitted to the surgical ward ward nerves and nerve during the month June 2014 until October 2014 that had a brain tumor the first time and met the inclusion criteria of data analysis using the chi-square test and Fisher in bivariate and multivariate analyzes followed by logistic regression. The number of subjects who met the inclusion criteria as much as 34 subjects. In bivariate analysis showed PPP p equal 0.023 (RP 7.556